Grace upon Grace - Wessels, Wessel (Stellenbosch Theological Journal, 2021)
Johan Cilliers relates that Grace upon Grace came to existence in his experience of "being retired of late", where he could "ponder the meaning of life from a different angle" (xi). On the one hand, Cilliers implies that Grace upon Grace does not have the purpose of academic contemplation. On the other hand, it takes one no time in interaction with Grace upon Grace to realise that Cilliers is indeed thoroughly grounded in contemplating the meaning of life in a sophisticated theological manner.